FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PREVALENSI KONTRASEPSI MODERN DI INDONESIA TAHUN 2017 - Sapriana Paskalina Fayon; Waris Marsisno (Politeknik Statistika STIS, 2020)
Contraceptive Prevalence Rate (CPR) is an indicator used to see how much contraceptive use is in an area, whereas modern CPR is an indicator that is specific to contraceptive use in a modern way. From 2015 to 2017, CPR figures for all methods and modern continue to decline and still not reach the target of the BKKBN even though the CPR target has been lowered. This study aims to analyze the factors that influence the prevalence rate of modern contraception by using multiple linear regression analysis methods, where the best model is chosen with the best subset regression method. The data used are secondary data obtained from the 2017 Indonesian Demographic and Health Survey (SDKI), 2017 District / City Poverty Data and Information, and the 2017 BKKBN Government Agency Performance Accountability Report. The analysis results show that the best model chosen is a model with variables free percentage of poor population, age of first marriage and knowledge of married men about contraception. Based on simultaneous tests, it can be concluded that there is at least one independent variable that is significant to the prevalence rate of modern contraception. While partially only the age of first marriage and the knowledge of married men about contraception are significant to the prevalence rate of modern contraception, where the age of first marriage has a negative effect and the knowledge of married men about contraception has a positive effect.